A New Chaotic System with Line of Equilibria: Dynamics, Passive Control and Circuit Design - Aceng Sambas; Mustafa Mamat; Ayman Ali Arafa; Gamal M Mahmoud; Mohamad Afendee Mohamed; W. S. Mada Sanjaya (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A new chaotic system with line equilibrium is introduced in this paper. This system consists of five terms with two transcendental nonlinearities and two quadratic nonlinearities. Various tools of dynamical system such as phase portraits, Lyapunov exponents, Kaplan-Yorke dimension, bifurcation diagram and Poincarè map are used. It is interesting that this system has a line of fixed points and can display chaotic attractors. Next, this paper discusses control using passive control method. One example is given to insure the theoretical analysis. Finally, for the  new chaotic system, An electronic circuit for realizing the chaotic system has been implemented. The numerical simulation by using MATLAB 2010 and implementation of circuit simulations by using MultiSIM 10.0 have been performed in this study.